Association of the eNOS 4a/b and -786T/C polymormphisms with coronary artery disease, obesity and diabetes mellitus - Kincl, V; Vasků, A; Meluzín, J; Panovský, R; Seménka, J; Groch, L (Folia biologica, 2009)
The aim was to assess the relationship between eNOS 4a/b and -786T/C polymorphisms with coronary artery disease (CAD), obesity and diabetes mellitus. Total number of 1313 patients underwent coronary angiography, 939 had significant CAD (stenosis of > or = 1 coronary artery > or = 50%), 222 had smooth coronary arteries. Patients with insignificant atherosclerosis were excluded, the study finally comprised 1161 patients. The analysis of eNOS 4a/b and -786T/ C polymorphisms was performed by polymerase chain reaction. No significant interaction was found between -786T/C polymorphism and solitary CAD or CAD with diabetes and obesity. For 4a/b polymorphism, genotypes aa+ab were almost three times more frequent in diabetic patients without CAD versus patients without CAD and without diabetes--OR 2.79; P = 0.009, Pcorr = 0.03. In 4a/b polymorphism and CAD with obesity and diabetes: bb genotype was significantly more frequent: in patients with CAD, diabetes and obesity in comparison with obese diabetic patients without CAD (OR = 3.63, Pcorr = 0.05); in non-diabetic non-obese patients with CAD, versus diabetic and obese patients without CAD (OR = 3.38, Pcorr = 0.05); in obese non-diabetic patients without CAD vs. obese diabetic patients without CAD (OR = 5.91, Pcorr = 0.01); in patients without CAD, obesity and diabetes vs. obese diabetic patients without CAD (OR = 3.59, Pcorr = 0.05). The eNOS 4a/b polymorphism has significant association with diabetes mellitus in CAD-negative patients, and with CAD in combination with obesity and diabetes mellitus. No association between 4a/b or -786T/C polymorphism and solitary CAD was found.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; obezita; rizikové faktory; Polymorphism, Single Nucleotide; Diabetes Mellitus; Humans; genetická predispozice k nemoci; genotyp; jednonukleotidový polymorfismus; Obesity; Risk Factors; Nitric Oxide Synthase Type III; diabetes mellitus; synthasa oxidu dusnatého, typ III; lidé; Genotype; nemoci koronárních tepen